Design of Experiments: A Tool for Statistical Analysis - Deep Patel; Sushant Dangat; Ashwin Kuchekar (Current Aspects in Pharmaceutical Research and Development Vol. 5, 2021)
In the world of new product development, Quality by Design (QbD) offers several benefits that can reduce hassle, increase efficiency, reduce regulatory compliance burdens, and build customer loyalty. A more stringent approach to the development of pharmaceuticals is applied by the FDA and Pharmaceutical industry. New pharmaceuticals should consider scientific, holistic, and risk-based approaches. When a company designs and develops a product, QbD elements are specified. The quality of methods and products is generally influenced by several input factors. Research has recently focused on understanding the effects of multidimensional and interconnected input factors on the outcomes of pharmaceuticals and analytical methods using the design of experiment (DoE). Additionally, it examines how DOE can be implemented, both for students and educators, and highlights historical perspectives on DOE. Good experimental design can help you make the most of the available resources and make it easier to analyze the results. Collaborations between researchers and practitioners that push the boundaries of experimental design are examined. It provides an overview of the principles and applications of the most common screening and response surface design, as well as the creation of mixed designs. To put it another way, the experimental design intends to minimize ambiguity and eliminate confusion. In a proper experimental design, relationships between and among variables are tested; in general, one variable, the independent variable, is controlled to quantify its effect on other variables. Dependent Control must be a core concern for any researcher using experimental design; in experiments, the researcher selects an intervention, which is linked to the independent variable, and then controls how that intervention is applied in the research context. If the experimental design is followed correctly, a causal relationship between the independent and dependent variables can be established.